2021
DOI: 10.26508/lsa.202000915
|View full text |Cite
|
Sign up to set email alerts
|

Viperin interacts with PEX19 to mediate peroxisomal augmentation of the innate antiviral response

Abstract: Peroxisomes are recognized as significant platforms for the activation of antiviral innate immunity where stimulation of the key adapter molecule mitochondrial antiviral signaling protein (MAVS) within the RIG-I like receptor (RLR) pathway culminates in the up-regulation of hundreds of ISGs, some of which drive augmentation of multiple innate sensing pathways. However, whether ISGs can augment peroxisome-driven RLR signaling is currently unknown. Using a proteomics-based screening approach, we identified Pex19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Proximity ligation assay was performed as described previously ( 55 ). Briefly, proximity ligation kits (Duolink PLA) were purchased from Sigma-Aldrich and the manufacturer’s protocol was followed.…”
Section: Methodsmentioning
confidence: 99%
“…Proximity ligation assay was performed as described previously ( 55 ). Briefly, proximity ligation kits (Duolink PLA) were purchased from Sigma-Aldrich and the manufacturer’s protocol was followed.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, following infection, MAVS is also found at regions of interaction between mitochondria and peroxisomes [421]. One report suggests that the viperin protein, through interactions with PEX19, repositions these two regions of MAVS localization more proximally to potentiate signaling [422]. MAVS interaction with the RLR triggers MAVS oligomerization and formation of a signalosome, with activation by one of two other MAM proteins, TNF receptor‐associated factor (TRAF) or inhibitor of kappa‐B kinase (IKK).…”
Section: Provisional Mam Subsetsmentioning
confidence: 99%
“…It has been observed that LDs that are in association with viperin can translocate to peroxisomes if this complex is not formed. It is difficult to find a peroxisome associated with LDs; this fact shows the importance of LDs in activating ISGs against viral infections [ 41 , 42 , 43 ]. While viperin can bind to other proteins to trigger an interferon response, it has been observed that it can only translocate to LDs to catalyze CTP conversion to ddhCTP, which is a ribonucleotide that serves as a terminator of viral RNA synthesis [ 44 ].…”
Section: Exploring the Multifaceted Roles Of Lipid Droplets And Their...mentioning
confidence: 99%